2014
DOI: 10.1176/appi.neuropsych.12100240
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Anxiety Among Patients With Early- Versus Late-Onset Alzheimer’s Disease

Abstract: The authors sought to evaluate the incidence and correlates of anxiety in early-onset Alzheimer's disease (EOAD) versus the more typical late-onset AD (LOAD). A group of 23 EOAD and 22 LOAD patients were compared by the Neuropsychiatric Inventory Anxiety subscale. Demographic and disease-related relationships with anxiety were evaluated, as well as types of anxiety symptoms that were endorsed. EOAD patients had significantly more anxiety symptoms than LOAD patients. Among those with EOAD, anxiety was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 33 publications
3
48
0
Order By: Relevance
“…Amyloid- β precursor protein ( A β PP ), presenilin 1 ( PSEN1 ), and presenilin 2 ( PSEN2 ) genes have been strongly implicated in early onset Alzheimer’s disease (EOAD), particularly familial EOAD, which comprise less than 5% of Alzheimer’s cases (15). In contrast, late onset Alzheimer’s disease (LOAD) has been associated with other genes including apolipoprotein E- ε 4 ( APOE ε 4 ), bridging integrator 1 ( BIN1 ) region, clusterin ( CLU ), phosphatidylinositol clathrin assembly lymphoid-myeloid ( PICALM ), and complement receptor 1 , mostly identified through genome-wide association studies (GWAS) ().…”
Section: Genetic Biomarkersmentioning
confidence: 99%
“…Amyloid- β precursor protein ( A β PP ), presenilin 1 ( PSEN1 ), and presenilin 2 ( PSEN2 ) genes have been strongly implicated in early onset Alzheimer’s disease (EOAD), particularly familial EOAD, which comprise less than 5% of Alzheimer’s cases (15). In contrast, late onset Alzheimer’s disease (LOAD) has been associated with other genes including apolipoprotein E- ε 4 ( APOE ε 4 ), bridging integrator 1 ( BIN1 ) region, clusterin ( CLU ), phosphatidylinositol clathrin assembly lymphoid-myeloid ( PICALM ), and complement receptor 1 , mostly identified through genome-wide association studies (GWAS) ().…”
Section: Genetic Biomarkersmentioning
confidence: 99%
“…Notably, Ossenkoppele et al (2015) recently reported that a subset of AD (and especially EOAD) patients have predominant behavioral and/or dysexecutive impairments, thus defining the so-called behavioral/dysexecutive variant of AD (Ossenkoppele et al, 2015). Few studies directly compared NPSs in EOAD and LOAD patients, but several lines of evidence and the reported clinical experience of the authors suggest that they are particularly severe in EOAD (Garre-Olmo et al, 2010; Kaiser et al, 2014; Ossenkoppele et al, 2015; Park et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…While the literature related to the impact of anxiety on specific AD-associated memory nuclei discussed by Bastin et al is not substantial, there is growing evidence of associations between anxiety and AD (Donovan et al 2018). Anxiety is a predictor for early onset AD (Kaiser et al 2014) and the conversion of mild cognitive impairment (MCI) to AD (Gallagher et al 2011). The importance of familiarity in early etiology and the accumulating observations of anxiety during this period suggests that an increased integrative focus on neural mechanisms of anxiety and familiarity, where nuclei involved in both processes are evaluated simultaneously, may provide valuable insight on the specific nature of the role of anxiety in susceptibility to MCI and AD, progression to AD, and the progression of AD symptomology.…”
Section: The Role Of Anxiety In the Integrative Memory Modelmentioning
confidence: 99%